Vulval hidradenoma papilliferum: a clinical and dermoscopic study. (1st December 2020) - Tosti, G.; Salvini, C.; Barisani, A.; Grazi, R.; Pirola, S.; Cantisani, C.; Vaccari, S.; Madnani, N.
Summary: Hidradenoma papilliferum (HP) is a rare, slow‐growing, benign adnexal tumour with apocrine differentiation. It usually affects the anogenital region in adult women and is clinically polymorphous, mimicking other benign or malignant neoformations. The dermoscopic features of vulval HP have not been reported yet. We report the clinical and dermoscopic features in a case series of histopathologically proven vulval HPs. Dermoscopy may be a useful tool for the diagnosis of vulval HP. To our knowledge, our paper represents the first report of dermoscopic findings in a series of vulval HPs in a multiracial population.